Dampak Apple Inc. Sebagai TNC terhadap Daya Saing dan Perkembangan Produk Lokal Advan di Indonesia - Rivki Aprilian; Muhammad Rifa; Rayhan Muhammad Akmal; Nazzir Abdul Majid; Septianis Afipah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study analyzes the impact of Apple Inc. as a transnational corporation on the competitiveness and development of local products produced by Advan in Indonesia through the lens of interdependence theory. Employing a qualitative descriptive approach based on secondary data, this research examines how global corporate dominance shapes local industrial dynamics. The findings indicate that Apple’s strong market position, supported by brand globalness, technological innovation, and integration into global value chains, generates competitive pressure on local producers. However, this pressure does not solely result in marginalization. Instead, it stimulates adaptive strategies among local firms, including product differentiation, price adjustments, and alignment with domestic consumer preferences. The study also highlights the strategic role of the Indonesian government in mediating global–local relations through industrial and regulatory policies such as the Local Content Requirement. Within the interdependence framework, the relationship between Apple and Advan reflects a complex interaction of competition and mutual reliance, where global firms depend on emerging markets while local industries leverage global standards as benchmarks for upgrading. This dynamic underscores the potential of transnational corporate presence to contribute to domestic industrial transformation when supported by coherent national policies.